Limited endoscopic mucosal inflammation on equivalent to Mayo endoscopic subscore of 0 unaffect clinical relapse of ulcerative colitis. (1st February 2022) - Shimodaira, Yosuke; Watanabe, Kenta; Fukuda, Sho; Watanabe, Noboru; Koizumi, Shigeto; Matsuhashi, Tamotsu; Onochi, Kengo; Iijima, Katsunori
Abstract: Background and aim: Mayo endoscopic subscore is a simple and validated endoscopic score for ulcerative colitis but the range of inflammation was not considered for scoring. There were few reports analyzing the range of inflammation for clinical relapse using Mayo endoscopic subscore (MES). The aim of this study is to investigate the relapsing potential of limited mucosal inflammation on endoscopic remission equivalent to MES of 0. Methods: For this retrospective observational study, ulcerative colitis patients underwent total colonoscopy were enrolled. Small mucosal lesion (SML) was defined as limited inflammation of range less than 3 cm. Clinical relapse was analyzed using the Kaplan–Meier curve with log-rank test, and factors associated with clinical relapse was analyzed using the cox proportional hazard regression model. Results: A total of 102 periods with mucosal healing or modified MES of 0 with SML were analyzed. In 12-months observation periods, clinical relapse occurred more frequently in MES of 1 than in MES of 0 or modified MES of 0 with SML, but it was comparable between MES of 0 and modified MES of 0 with SML. When compared to patients with modified MES of 0 with SML, the hazard ratio in patients with MES of 1 (6.55; p = .028) was significantly high but similar in those with MES of 0 (2.59; p = .29). Conclusions: Small mucosal inflammation in UC does not affect the clinical relapse if most of the mucosa achieved a score similar to MES of 0.